Slavery and Early Christianity - a reflection from a human rights perspective - P. G. Kirchschlaeger (Acta Theologica)
Addressing the topic “slavery and Early Christianity” is a difficult task for various reasons. First, it is complex to reach an understanding of slavery of that time. Secondly, there is the hermeneutic challenge of approaching the issue with a current mind-set that includes the notion of the abolition of slavery. Furthermore, from a contemporary perspective, a critical account of slavery and Early Christianity is possible, with the temporal distance protecting one from the consequences linked to a judgement about slavery. Finally, there is the hermeneutic challenge of engaging with texts from Early Christianity from an ethical perspective in order to reach present-day normative propositions, while respecting the original intention of the texts. In light of these challenges, this article will offer a brief overview of opinions on slavery in Hellenistic philosophy and in the Jewish tradition, and then discuss slavery and Early Christianity, followed by a reflection on slavery and Early Christianity from a human rights perspective.